Awareness Is Not Enough: A Double-Blind Randomized Controlled Trial of the Effects of Providing Discipline Disproportionality Data Reports to School Administrators. (October 2020) - McIntosh, Kent; Smolkowski, Keith; Gion, Cody M.; Witherspoon, Lauren; Bastable, Eoin; Girvan, Erik J.
One commonly used strategy used in attempts to decrease racial disproportionality in school discipline across the country is sharing data with school administrators that discipline disparities are a problem in their schools with the assumption that it will increase attention to equity and improve outcomes. The purpose of this study was to assess the effects of providing monthly disciplinary equity reports to school administrators in 35 schools on levels of (a) disciplinary equity report viewing, (b) disciplinary equity, and (c) inclusion of disciplinary equity into school improvement plan goals. We used a small, double-blind randomized controlled trial in which half of the schools were randomly assigned to receive either monthly disciplinary equity reports or monthly general discipline reports. Results showed that schools receiving the equity reports had significantly increased rates of viewing equity reports but no meaningful change in disciplinary equity or equity goal setting.